2022
DOI: 10.28991/cej-2022-08-05-012
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Mechanical Properties of Green Concrete

Abstract: Green concrete is a type of concrete that uses waste materials as one of its ingredients. Hazardous wastes like fly ash and silica fume can be used to partially replace cement in concrete, which varies in physical and chemical properties. On the other hand, the increase in automobiles in urban and rural areas has led to an increase in the number of waste tires, which promotes environmental pollution due to disposal issues throughout the world. This study aims to use waste materials which can partially replace … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Al-Omari & Al-Mashhadani [3] discovered that increasing the amount of stone powder in concrete increased the compressive strength of the material up to a certain point. The inclusion of stone powder was also identified in the investigation by Islam & Hossain [4].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Al-Omari & Al-Mashhadani [3] discovered that increasing the amount of stone powder in concrete increased the compressive strength of the material up to a certain point. The inclusion of stone powder was also identified in the investigation by Islam & Hossain [4].…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, multiple studies have indicated that the inclusion of stone powder can increase the flexural and compressive strength of concrete. From an economic standpoint, incorporating stone powder into concrete can help reduce the cost of cement mixtures [3,4]. However, it is important to note that the literature also highlights certain drawbacks of using stone powder, such as potential variations in quality, which can impact workability, and a potential decrease in abrasion resistance if high fractions are employed [5].…”
Section: Introductionmentioning
confidence: 99%
“…Without causing any negative effects, the catalytic cracking catalyst may be used to replace 10% of the sand or 15% to 20% of the cement content [18,19]. To strengthen the strength of structural elements, ferrocement was adhered to their surfaces [ 20,21]. It reduces concrete permeability and prevents cracking brought on by drying shrinkage and thermal expansion [22].…”
Section: Spent Catalystmentioning
confidence: 99%